2019
DOI: 10.1016/j.pec.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

How and when do patients request life-expectancy estimates? Evidence from hospice medical consultations and insights for practice

Abstract: Clinicians should be mindful that rather than overtly requesting estimates, patients may seek them more cautiously. Before delivering estimates, doctors can support patients to articulate their existing understanding and perspective regarding prognosis, and their readiness to hear more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…26,27 An example of this was the design of time estimate requests as seeking opinions rather than facts, minimising the apparent burden of the request. 28 A similar finding was seen in Pino and Parry's study of hospice consultations with patients; 29 however, in that study, there was more work to 'prepare the conversational environment' for a prognostic estimate, including doctors checking patients' existing knowledge and readiness. This difference may reflect relatives' stronger entitlement to prognostic information and increased clinician responsibility to provide it at the very end of life.…”
Section: Key Findingssupporting
confidence: 53%
“…26,27 An example of this was the design of time estimate requests as seeking opinions rather than facts, minimising the apparent burden of the request. 28 A similar finding was seen in Pino and Parry's study of hospice consultations with patients; 29 however, in that study, there was more work to 'prepare the conversational environment' for a prognostic estimate, including doctors checking patients' existing knowledge and readiness. This difference may reflect relatives' stronger entitlement to prognostic information and increased clinician responsibility to provide it at the very end of life.…”
Section: Key Findingssupporting
confidence: 53%
“…19 Although providing these opportunities does not guarantee a patient or family member will raise illness progression or end of life, there are documented instances where patients take the opportunity to raise these matters. 27,28 Oncology consultations 32,39,60,61 Palliative care 27 Internal medicine 44 Everyday conversations 62 How clinicians seek a patient or family member's perspective about a specific matter All rights reserved. No reuse allowed without permission.…”
Section: How Clinicians Provide Opportunities For Patients or Family mentioning
confidence: 99%
“…This is particularly the case when the person being discussed is either involved in the conversation or is a significant for one or more parties to the conversation. 28,32,34,41 How clinicians, patients, and family members refer explicitly to the future In contrast to practices that discuss future deterioration and end of life indirectly, these studies explore instances where such matters are made explicit. On some occasions, discussions about end of life were initiated by clinicians indirectly, and subsequently made explicit by patients.…”
Section: How Clinicians Provide Opportunities For Patients or Family mentioning
confidence: 99%
“…Having identified that nurses caring for liver patients need to be equipped to help support many complex situations, attention to providing the underpinning education and training in communication skills is essential to increase both confidence and competence in having these conversations. Recent developments in conversational analysis have shown that both professionals and patients are hesitant to introduce the topic of end-of-life discussions, for numerous reasons (Pino and Parry, 2018). During consultations, patients are often reluctant to ask for an estimated prognosis or broach the subject of dying, instead waiting for open opportunities to appear.…”
Section: Nurse Trainingmentioning
confidence: 99%
“…During consultations, patients are often reluctant to ask for an estimated prognosis or broach the subject of dying, instead waiting for open opportunities to appear. Patients can be encouraged by understanding their perspective and readiness to hear more (Pino and Parry, 2018). Nurses often fear that raising this topic may not be their role or responsibility, this it is something that all health professionals involved in end-of-life care share responsibility for, and nurses are most suitably placed than other colleagues, being more likely to know their patients and associated loved ones well.…”
Section: Nurse Trainingmentioning
confidence: 99%